(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigated the impacts of Multimedia Technology Instruction on public secondary school students’ motivation and achievement in Mathematics in Federal Capital Territory, Abuja, Nigeria. Three research questions and hypotheses guided the study. The research design employed was quasi-experimental design of pre-test, post-test non-randomized and control group. The population of the study was made up of 10,936 SS II students. Multi-stage sampling technique was used to select 125 SS II students comprising both experimental (60) and control (65) groups. The research instruments used for data collection were Students’ Motivation (SMQ) and Mathematics Achievement Test (MAT). The instruments were validated and subjected to reliability test and internal consistency of 0.799 and 0.859 were obtained for SMQ and MAT using Cronbach Alpha and Kuder-Richardson formula 21 (K-R21) respectively. Data collected were analysed using mean rank for research questions one, mean and standard deviation for research questions two and three while Mann-Whitney U test was used to test hypothesis one and ANCOVA was used for testing of hypotheses two and three at 0.05 levels of significance. The findings revealed that mean motivation scores of students in experimental group were higher than those in control group, there was significant difference between the mean achievement scores of students taught Mathematics using MTI and those taught using conventional method; female students performed better than the male students in terms of achievement in the experimental group. Based on the findings, it was recommended among others that implementation of experimental intervention used in this study should be implemented in all schools since it improves students’ motivation; secondary schools should adopt MTI as a primary teaching approach in Mathematics as it significantly enhances students’ achievement compared to conventional method of teaching; teachers and curriculum developers should design gender-responsive teaching strategies within MTI to further support and enhance the performance of male students.